Diagnosis and mapping of diminazene aceturate resistance in Trypanosoma congolense, Broden 1904, strains circulating in cattle in Matutuíne district, Mozambique - Neves, Luís C.B.G. (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2014.